Bellaso's 1552 cipher recovered in Venice. Issue 6 (2nd November 2019) - Bonavoglia, Paolo
Abstract: In his 1553 paper Giovan Battista Bellaso presented his first polyalphabetic cipher, writing that this was an improved reprint of a previous cipher of 1552 that had been printed in Venice on a loose leaflet without instructions. There was much speculation about this early cipher, since no print of that cipher was reported to have been found. Now a printed copy of that leaflet has been found in Venice by the author, and this paper is a report of that finding.